Locally advanced non-small cell lung cancer treatment: another step forward - Filosso, Pier Luigi; Guerrera, Francesco; Lausi, Paolo Olivo; Ruffini, Enrico (Journal of Thoracic Disease, 2017)
Despite several revisions of the TNM lung cancer staging system, the N2 descriptor still brings together in one single category, a very different group of patients with dissimilar overall prognosis, ranging from microscopical/small single station N2 to multiple/bulky disease (1,2). At one end of this spectrum, the disease appears to be resectable, whilst, at the other end, it is obviously unresectable.